The influence of IS1301 in the capsule biosynthesis locus on meningococcal carriage and disease. - Kugelberg, E; Gollan, B; Farrance, C; Bratcher, H; Lucidarme, J; Ibarz-Pavon, AB; Maiden, M; Borrow, R; Tang, C (Public Library of Science, 2010)
Previously we have shown that insertion of IS1301 in the sia/ctr intergenic region (IGR) of serogroup C Neisseria meningitidis (MenC) isolates from Spain confers increased resistance against complement-mediated killing. Here we investigate the significance of IS1301 in the same location in N. meningitidis isolates from the UK. PCR and sequencing was used to screen a collection of more than 1500 meningococcal carriage and disease isolates from the UK for the presence of IS1301 in the IGR. IS1301 was not identified in the IGR among vaccine failure strains but was frequently found in serogroup B isolates (MenB) from clonal complex 269 (cc269). Almost all IS1301 insertions in cc269 were associated with novel polymorphisms, and did not change capsule expression or resistance to human complement. After excluding sequence types (STs) distant from the central genotype within cc269, there was no significant difference for the presence of IS1301 in the IGR of carriage isolates compared to disease isolates. Isolates with insertion of IS1301 in the IGR are not responsible for MenC disease in UK vaccine failures. Novel polymorphisms associated with IS1301 in the IGR of UK MenB isolates do not lead to the resistance phenotype seen for IS1301 in the IGR of MenC isolates.